2022
DOI: 10.1002/ldr.4435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restoration of degraded lands on soils physicochemical properties and adaptability of planted woody species in southwestern Niger

Abstract: This study examines the effects of restoration of degraded lands on soils physicochemical properties and adaptability of planted woody species over a period of 4-6 years. It is based on: (1) Physicochemical analyses of soils (granulometry, calcimetry, and organic matter); (2) measures carried out for the dimensioning of anti-erosion structures;(3) dendrometric measurements on planted woody species on a density from 96 to 625 plants/ha, and the excavations of their root systems. The soils are characterized by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Fast-growing poplar is a clone of Populusnigra L, which grows rapidly, has strong ability to resist natural disasters, and can quickly improve site conditions 20 , 21 . It is widely used in land restoration 22 , 23 . The input of organic matter as an effective method to increase soil organic matter, Bednik et al 24 showed that biochar can help to improve the fertility of sandy substrates and provide suitable conditions for vegetation restoration during reclamation.…”
Section: Introductionmentioning
confidence: 99%
“…Fast-growing poplar is a clone of Populusnigra L, which grows rapidly, has strong ability to resist natural disasters, and can quickly improve site conditions 20 , 21 . It is widely used in land restoration 22 , 23 . The input of organic matter as an effective method to increase soil organic matter, Bednik et al 24 showed that biochar can help to improve the fertility of sandy substrates and provide suitable conditions for vegetation restoration during reclamation.…”
Section: Introductionmentioning
confidence: 99%